2022
DOI: 10.1101/2022.01.23.477413
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The amyloid precursor protein modulates the position and length of the axon initial segment offering a new perspective on Alzheimer’s disease genetics

Abstract: The small Aβ peptide has been hypothesized to be the main driver of Alzheimer's disease (AD). Aβ is a proteolytic cleavage product of a larger protein, the amyloid precursor protein (APP), whose normal functions remain largely unexplored. We report here activities of the full-length APP protein that relate directly to the etiology of AD. Increasing neuronal activity leads to a rapid increase in App gene expression. In both cultures of mouse cortical neurons and human iPSC-derived neurons, elevated APP protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 75 publications
(78 reference statements)
0
2
0
Order By: Relevance
“…Cultured neurons express βIII tubulin throughout the cell, but not as strongly in axonal processes ( 34 ). We previously found that processes in human iN cells stained for ankyrin G, identifying the axonal initial segment, which similarly lacked βIII-tubulin ( 35 ). Detection of GIRK2 primarily on βIII-tubulin + /MAP - processes, therefore, suggests pre-axonal, and likely presynaptic, localization.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cultured neurons express βIII tubulin throughout the cell, but not as strongly in axonal processes ( 34 ). We previously found that processes in human iN cells stained for ankyrin G, identifying the axonal initial segment, which similarly lacked βIII-tubulin ( 35 ). Detection of GIRK2 primarily on βIII-tubulin + /MAP - processes, therefore, suggests pre-axonal, and likely presynaptic, localization.…”
Section: Resultsmentioning
confidence: 99%
“…Cultured neurons express βIII tubulin throughout the cell, but not as strongly in axonal processes 57 . We previously found that processes in human iN cells stained for ankyrin G, identifying the axonal initial segment, which similarly lacked βIII-tubulin 58 .…”
Section: Gene Expression Patterns Predict Functional Differences Betw...mentioning
confidence: 94%